A decade of retail regulation in Spain (Ciudades, 2018)
Retail laws come out to solve the problems generated by new trade formats. First,they were similar to the French model, the law Royer, in order to control the growth of the superstores. Later, Retail Planning began, with Retail Equipment Plans to fit uses of land and Plans for the modernization of retail systems to modify networks of existing stores, giving grants to retailers. The reasons for the retail policies are based on commercial purposes and they are not connected to urban or territorial planning. The Bolkestein guidelines, dated 2006, removed obstacles for locations of large firms in fixed places. Authorizations for new retail locations must respect general interest, trying to reach enterprise efficiency.Government policies have also originated unexpected effects, like decreasing hypermarkets, increasing retail parks and supermarkets, and encouraging enterprises concentration.
Keywords: urban retail; Retail Planning Law